2002
DOI: 10.1051/0004-6361:20020460
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the distribution of HII regions in external galaxies

Abstract: Abstract.We have compiled a new sample of galaxies with published catalogs of HII region coordinates. This sample, together with the former catalog of García-Gómez & Athanassoula (1991), will form the basis for subsequent studies of the spiral structure in disc galaxies. In this paper we address the problem of the deprojection of the galaxy images. For this purpose we use two deprojection methods based on the HII region distribution and compare the results with the values found in the literature using other de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 99 publications
(66 reference statements)
1
24
0
Order By: Relevance
“…Both the figures and tables show that the PA values are better determined in a statistical sense than the IA values, in good agreement with what was already found by García-Gómez & Athanassoula (1991) and García-Gómez et al (2002). The mean correlation coefficient for the PA values is 0.86, while the mean correlation coefficient for the IA is 0.81.…”
Section: Comparison Of the Deprojection Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Both the figures and tables show that the PA values are better determined in a statistical sense than the IA values, in good agreement with what was already found by García-Gómez & Athanassoula (1991) and García-Gómez et al (2002). The mean correlation coefficient for the PA values is 0.86, while the mean correlation coefficient for the IA is 0.81.…”
Section: Comparison Of the Deprojection Methodssupporting
confidence: 90%
“…In this paper we introduce two methods, based on the Fourier transforms and which are closely linked to the two methods used by García-Gómez et al (2002) for HII region distributions. Let I(u, θ) be the image of the galaxy written in polar coordinates (r, θ), and u = ln(r).…”
Section: Deprojection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface density distributions of H ii regions in spiral galaxy disks can also be represented reasonably well by an exponential function (e.g., Hodge & Kennicutt 1983;Athanassoula et al 1993;García-Gómez et al 2002), the exceptions being mainly due to unsatisfactory fits of the maxima near the center. Athanassoula et al found that the H ii regions are marginally more concentrated to the centers of spiral galaxies than are the disk stars, with a ratio of scale lengths of h H ii /h is 0.8 ± 0.4.…”
Section: Isophotal Radius Normalizationmentioning
confidence: 99%
“…Throughout this work, we measure the pitch angle P of the m = 2 component. Pitch angles are determined from peaks in the Fourier spectra, as this is the most powerful method to find periodicity in a distribution [24,25].…”
Section: Measurement Of Spiral Arm Pitchmentioning
confidence: 99%